Immunohistochemistry in Tumor Diagnostics - Tuffaha, Muin S.A (Springer International Publishing, 2018)
This book offers a comprehensive yet concise overview of immunoprofile of tumors and antibodies used in contemporary surgical pathology, and provides diagnostic algorithms for approaching tumor diagnostics. Immunohistochemistry has become the most important ancillary technique in diagnostic pathology in the last 20 years, and unlike most books on tumor diagnostics, this volume discusses in details immunohistochemical biomarkers, diagnostic approaches and their pitfalls, as well as the immunoprofile of common tumors throughout all systems of human body. With numerous color figures and detailed flowcharts, it appeals to all pathologists be they young residents in training who want a brief introduction to this technique, or specialists in need of a reliable and comprehensive reference resource in tumors diagnostics.